HUBUNGAN ANTARA KOMUNIKASI ORANG TUA-ANAK DAN REGULASI DIRI DENGAN KEDISIPLINAN SISWA BOARDING SCHOOL SMP IT AL HUDA WONOGIRI - Baqiyyatush Sholihah; Hardjono Hardjono; Mahardika Supratiwi (Program Studi S1 Psikologi, 2019)
Boarding school is a system known as a place for forming the character of discipline and independence of students. Discipline is a behavior consciously and seriously to obey the rules according to applicable norms. Problems with discipline at the Boarding School include, for example, fighting, smoking, dating, going out of the compound not permitting, and carrying electronic equipment. Discipline is influenced by matters related to external influences such as parent-child communication and is influenced by internal influences such as self-regulation. The purpose of this study was to determine the relationship between parent-child communication and self-regulation with discipline in boarding school students at SMP IT Al Huda Wonogiri. The approach in this study uses correlational quantitative. The sample in this study was 186 students selected through proportional stratified random sampling. The research data was obtained with three scales, namely the discipline scale with r = 0.912, the parent-child communication scale with r = 0.922, and the self-regulation scale with r = 0.834. The analysis technique used is multiple linear regression analysis and correlation test. The conclusion of this study is that there is a relationship between parent-child communication and self-regulation with discipline in boarding school students at SMP IT Al Huda Wonogiri (Fcount > Ftable (26,261 > 3,045); p = 0,00; and R = 0,472 ) Partially there is a significant relationship between parent-child communication with discipline (rx1y = 0.316; p = 0.000 < 0.05), and self regulation is also significantly associated with discipline (rx2y = 0.151; p = 0.040 < 0.05) . R2 value is 0.223, so in this study parent-child communication and self-regulation together have an effective contribution to discipline of 22.3%.